(untitled) (Journal of the College of Education for Women, 2022)
Citizenship education is the effective educational tool in building a citizen who is able to participate in building his country. This can only come through the educational efforts that teachers make in the classroom. Such a step requires teachers to have knowledge of citizenship education, its principles, and the foundations for its development. Thus, the study aims to examine the degree of social studies teachers’ knowledge of the dimensions of citizenship education at the basic education schools in the Sultanate of Oman. It also aims to examine its relationship with a set of variables. The researchers used the quantitative descriptive approach to achieve the objectives of the study. It further adopted a test tool, which consisted in its final form of five areas: citizenship knowledge, rights and duties, national identity, community partnership, and global and digital citizenship. The test was divided later into (38) multiple-choice questions. After verifying the validity and reliability of this tool, it was applied to a sample of (200) male and female teachers. The results of the study have shown that the degree of knowledge of social studies teachers in citizenship education was average, reaching the arithmetic level of (57.67%). Furthermore, there were no statistically significant differences in the level of knowledge of social studies teachers of citizenship education with respect to the variables of gender and educational qualification in the fields of citizenship education. Accordingly, the researchers have recommended that the citizenship education course should be included in teacher preparation programs at public and private universities in the Sultanate of Oman. Moreover, the concepts and principles of citizenship education should be included in the school curricula.